Post-Pandemic Social Resilience: A Qualitative Review of International and National Policy Frameworks - Wan Muna Marwah; Erick Imanuel; Elinda Novita Dewi (Anthroposia: Journal of Social and Human Development, 2026)
This study examines how post-pandemic social resilience is constructed across international and national policy frameworks using a qualitative interpretive review. Drawing on policy documents and scholarly analyses published between 2020 and 2025, the research applies comparative discourse analysis to identify how resilience is defined, institutionalized, and translated into governance priorities. The findings show that international frameworks frame resilience as systemic transformation linking sustainability, social equity, and institutional learning, whereas national policies tend to operationalize it as administrative stabilization focused on economic recovery and service continuity. The analysis further reveals that policy effectiveness depends on the interaction between governance instruments, social infrastructures, and organizational adaptability, with fragmented approaches often reinforcing existing inequalities. By conceptualizing resilience as a relational governance discourse rather than a measurable endpoint, the study contributes to social development theory and demonstrates the analytical value of policy narrative comparison for understanding post-crisis transformation. The article offers methodological insight for qualitative policy research and highlights the importance of integrated welfare, digital governance, and psychosocial support in shaping inclusive recovery trajectories across diverse institutional contexts and future crisis preparedness agendas globally.